HUBUNGAN TINGKAT PENDIDIKAN IBU HAMIL TERHADAP FREKUENSI PEMERIKSAAN KEHAMILAN BPM G. N. MAYA D. TAMBAK SAWAH: HUBUNGAN TINGKAT PENDIDIKAN IBU HAMIL TERHADAP FREKUENSI PEMERIKSAAN KEHAMILAN BPM G. N. MAYA D. TAMBAK SAWAH - Andarwulan, Setiana (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2019)
Antenatal care is a health service carried out by a health worker to a mother during her pregnancy in accordance with established antenatal care standards. The use of antenatal care services by a number of pregnant women in Indonesia has not been fully in accordance with established guidelines. The lack of use of antenatal care by pregnant women is related to many factors. One of the factors is the education of pregnant women. The purpose of this study was to determine the relationship of the education level of pregnant women with the frequency of antenatal care at BPM G. N. Maya D Tambak Sawah. The research was carried out in May - July 2019. The research was carried out by cross sectional method, which has research variables, namely the level of education and the frequency of antenatal care. Total population of 36 pregnant women while the sample of 33 pregnant women. Data collection is done by filling out questionnaires made by researchers and filled out by respondents. Furthermore, the data collected was processed using SPSS version 20 computer program help to be analyzed by Chi-square test with a significance level (Î±) of 0.05. The results showed a low level of education as much as 54.5% frequency of pregnancy check irregularities as much as 54.5%, the relationship between the level of education and the frequency of antenatal care was x2 = 33> from x2 table = 5.99. The conclusion in this study there was a relationship between the level education of pregnant women with the frequency of antenatal care.